Coagulation Factor Plasma Levels Following Administration of a 4-Factor Prothrombin Complex Concentrate for Rapid Vitamin K Antagonist Reversal in Japanese Patients - Masahiro Yasaka, MD; Andres Brainsky, MD; Peijin Zhang, PhD; Shigeki Kushimoto, MD (Elsevier, 2018)
ABSTRACT: Background: Four-factor prothrombin complex concentrates (4F-PCCs) have been approved for urgent vitamin K antagonist reversal in Western countries for many years. Ethnicity and genetic variations between populations may influence the pharmacokinetic profile of 4F-PCC treatments. Objective: To report plasma levels of vitamin K-dependent coagulation factors and proteins C and S in Japanese patients following administration of a 4F-PCC approved recently in Japan. Methods: This was a subanalysis of a prospective, open-label, Phase IIIb study in Japanese patients requiring rapid vitamin K antagonist reversal owing to major bleeding (n = 6) or need for urgent surgery (n = 5). International normalized ratio and plasma levels of factors II, VII, IX, and X, and proteins C and S were measured before PCC infusion and at specific time points for the next 24 hours. Adverse events and serious adverse events were recorded up to Day 14 and 45, respectively. Results: Rapid increases in plasma concentrations 30 minutes following 4F-PCC infusion were seen for all factors and proteins C and S, with median concentrations compared with baseline increasing by ≥100% and 70% in the bleeding and surgical groups, respectively. A concurrent decrease in international normalized ratio was observed. Plasma levels for each factor and protein remained within physiologic levels throughout the assessment period. No relationship between thromboembolic events and elevated plasma levels was identified. Conclusions: Administration of 4F-PCC in Japanese patients receiving vitamin K antagonist anticoagulation therapy resulted in rapid and sustained increases in plasma levels and was well tolerated, indicating that this treatment is effective for the urgent reversal of vitamin K antagonist therapy in this population. Key words: Coagulation factor, Hemorrhage, Prothrombin complex concentrate, Surgery, Vitamin K antagonist